Enhancing EFL Teaching Skills: An Auto-Ethnographic Online Professional Development Journey - Hery Yanto The (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Modern technology has altered English as a Foreign Language (EFL) instruction, opening new options for creativity and greater learning. Teachers of English as a Foreign Language (TEFL) can update their knowledge of best teaching practices and adapt to new challenges in the field by taking advantage of open, online resources. This auto-ethnographic study serves as a thorough resource for EFL educators, illuminating the procedure of selecting suitable online platforms and learning methodologies to correspond with the needs of the digital age. This study utilizes auto-ethnographic methodologies to examine the cognitive shifts and adaptive strategies involved in integrating conventional teaching practices with cutting-edge technology. Educators of foreign languages interested in self-directed professional development can gain knowledge from this study. Educators are advised to actively participate in self-directed learning pursuits, leveraging an extensive array of online resources. This study contributes to the ongoing discourse surrounding auto-ethnography, online learning, and the pedagogy of teaching English as a foreign language by providing a first-person narrative that is grounded in theoretical frameworks. Ultimately, this highlights the transformative capacity of digital platforms in the context of EFL teaching, as it promotes continuous learning and adaptability among educators.